A Mathematical Model to Describe the Melanoma Dynamics Under Effects of Macrophage Inhibition and CAR T-cell Therapy - Rodrigues, G.; da Silva, J. G.; Santurio, D. S.; A. Mancera, P. F. (Trends in Computational and Applied Mathematics, 2024)
Melanoma is considered one of the most aggressive types of cancer due to its high propensy for metastasis, which significantly reduces survival chances when detected late. Moreover, melanoma exhibits strong immunogenic characteristics, complicating its treatment, increasing the need to develop more effective techniques of therapy. In the field of oncology, mathematical modeling enables the analysis and distinction of the various mechanisms involved in tumor progression. This allows the analysis of numer- ous scenarios, which would be impractical experimentally. The main objective of this study is to develop a mathematical model that describes melanoma dynamics in the presence of Tumor-Associated Macrophages (TAM) and Chimeric Antigen Receptor (CAR) T-cell immunotherapy. The goal is to assess why this therapy often falls short in erradicating solid tumors like melanoma and to understand the role of TAM in this failure. This research encompasses stability analysis of the equilibrium points of the model, sensitivity analysis of its parameters, and the examination of numerical solutions. Our results showed that immunosuppression caused by TAM has a negative impact on the effectiveness of the dose and varying the cytotoxicity of CAR T-cells together with dose. Adjusting CAR T-cell cytotoxicity and treatment dosage may enhance tumor control, with the initial tumor burden playing a crucial role in treatment effectiveness.